A darker domain - McDermid, Val (London , Harper Colins, 2008)
Twenty-five years ago, the daughter of the richest man in Scotland and her baby son were kidnapped and held to ransom. But Catriona Grant ended up dead and little Adam's fate has remained a mystery ever since. When a new clue is discovered in a deserted Tuscan villa, along with grisly evidence of a recent murder, cold case expert DI Karen Pirie is assigned to follow the trail. She's already working a case from the same year. During the Miners' Strike of 1984, pit worker Mick Prentice vanished. He was presumed to have broken ranks and fled south with other 'scabs', but Karen finds that the reported events of that night don't add up. Where did he really go? And is there a link to the Grant mystery? The truth is stranger and far darker than fiction
A level
Keywords: Fiction